Perancangan Arsitektur Jaringan Body to Body dan Model Interoperabilitas untuk Transmisi Data Biomedis dari Sinyal Sensor Elektroensefalografi - Anggara, Wahid Afiq; Wahidah, Ida; Santoso, Iman Hedi (eProceedings of Engineering, 2024)
The brain is one of the most important organs in the human body since it is the center of human equilibrium and the place of human balance. Human brain activity examination is highly suggested as the examination enhances a person's physical and mental state, such as by monitoring brain and mental health, early identification of sickness, and testing cognitive and emotional problems. With the high probability of increasing the number of people who experience decreased brain function, it can be concluded that a system solution that can be proposed for this problem is by designing an EEG (electroencephalogram). EEG (electroencephalogram) is an instrument that measures electrical activity in the human brain. EEG can be used to look for abnormal brain wave patterns that indicate errors and other abnormalities. EEG analysis is one method that aids in the process of assessing brain activity. Besides that, the use of Neurosky as an EEG is also very helpful where the tool has a Neurosky eSense, which can read a person's level of focus to meditation. The results of our research using NeuroSky Mindwave, which is connected to the Arduino UNO microcontroller, can produce brain activity data in the form of